Small vessel vasculitis: a rare case report - Asutkar, Pradnya; Pande, Sushil (International Journal of Research in Dermatology, 2023)
Small-vessel vasculitis is a rare immunological disease that affects arterioles, capillaries and venules. A 1-year-6-month-old male of non-consanguineous marriage came to the OPD with his mother with a complaint of swelling over bilateral legs for 3 days and rash over his body for 1 day. The swelling was increasing and gradually ascending upward. Systemic examination revealed S1, S2 +, and no murmur in CVS. Soft, NT, liver, spleen not palpable. The patient was admitted and routine investigations were sent. The case reported above had clinical spectrum with skin involvement as palpable purpura, nervous system involvement as peripheral neuropathy and proximal myopathy and hematological involvement, gastrointestinal involvement as vague abdominal pain.